Produzindo a Vida: O etnoconhecimento da agricultura familiar na comunidade Nossa Senhora Aparecida da Costa do Juçara, município de Coari-AM. - Menezes, Gleides Medins de (2019)
ABSTRACT The present work talk about with the traditional knowledge practiced up to the present day by the peoples living on the banks of the rivers, lakes and streams of the Amazon region, inherited from our indigenous ancestors. The discussion and conceptual analysis started from a qualitative approach of the observation and understanding of these knowledge in the social context of economic relations and affectivity of the work organization. Our research was carried out in the rural community called „Nossa Senhora Aparecida da Costa do Juçara‟, located on the left bank of the Solimões River, approximately 5,700 km of the municipality Coari, in the State of Amazonas, where work processes in family farming have contributed to maintenance of families in the community. Our objective was to analyze the ethnoknowledge used in the work processes of the várzea farmers in the community, to maintain the material and symbolic way of life, problematizing central issues such as resistance to the current capitalist mode of production and the maintenance of a socio-biological diversity that local bio ecosystem. Characteristic aspects of the transition from a conventional agriculture to an ecologically based agriculture are present in the ethnoknowledge adopted by the community, in the techniques of soil and vegetation management for the production of vegetables and fruits through family agriculture. Keywords: Ethnoknowledge; job; family farming;